LITERATURE REVIEW ON THE USE OF PROBLEM BASED LEARNING MODELS IN IMPROVING PHYSICS LEARNING OUTCOMES - Mila Candra Pristianti; Binar Kurnia Prahani (INSECTA: Integrative Science Education and Teaching Activity Journal, 2023)
The purpose of this study is to describe the use of PBL models to improve student learning outcomes. This research method uses library research. The data studied were obtained from Google Scholar and Scopus from 2018 to 2022. The scope of the data analyzed is physics learning with the PBL model and its relationship to enhancing learning outcomes. The descriptive qualitative analysis was used to analyze the data. The results of this study indicate that PBL can be effectively implemented in physics learning. This learning can increase student activity in class because it involves students directly participating in solving the problems given and can increase students' understanding of physics. With increasing student understanding, student learning outcomes also increase. This learning can be done by applying different technologies such as digital books, 3D, PhET, and augmented reality. From this study, the PBL models can be used to improve student learning outcomes in face-to-face, mixed, and online learning. Future research can be carried out by directly implementing the PBL model to determine its effect on student problem-solving skills and critical thinking.